Spleen-sparing excision of giant splenic hydatid cyst - L. Jarray; M. Boughdir; W. Maamatou; A. Daid; R. Ben Abdallah; S. Tlili; Y. Hellal; Y. Gharbi; N. Kaabar (Elsevier, 2022)
Introduction: Splenic echinococcosis is a rare disease even in endemic regions such as the Mediterranean. The organs most involved are the liver and the lungs. However, other organs can be affected, such as the spleen. To our knowledge, primary involvement of the spleen is very rare, and a few cases of splenic hydatidosis (SHD) isolated in children have been reported. Splenectomy used to be the reference treatment, but it is now being questioned, first by the current trend towards conservative surgery, especially for a benign pathology and by the knowledge of postoperative complications. We report a case of a giant hydatid cyst of the spleen that underwent conservative surgery in the department of pediatric surgery at HabibThameur Hospital in Tunis. Case presentation: A 9-year-old girl, without any notable pathological history, coming from a rural environment with notion of contact with animals, who consulted for isolated recurrent abdominal pain evolving since six months. The examination showed a soft, painless abdomen with amarked splenomegaly. In view of a pauci-symptomatic clinical picture, a negative hydatic serology, a chest X-ray without abnormalities and the results of the ultrasound and abdominal computed tomography, the diagnostic of epidermoid cyst of the spleen was the most likely, especially with the primary location. Intraoperative findings did not match epidermal cyst and hydatic cyst was suspected. The puncture of the cyst brought back a clear liquid "rock water". The "PAIR" technique with pericystectomy and epiploplasty was performed. Anatomopathological examination confirmed the diagnosis. The postoperative course was uneventful. Conclusion: The diagnosis of splenic hydatidosis must be evoked ahead of any cyst of the spleen especially in endemic countries. The choice of surgical technique is controversial. In children, conservative surgery is always preferable and is currently recommended by most authors.